Serotonergic Input to Orexin Neurons Plays a Role in Maintaining Wakefulness and REM Sleep Architecture - Saito, Yuki C.; Tsujino, Natsuko; Abe, Manabu; Yamazaki, Maya; Sakimura, Kenji; Sakurai, Takeshi (Frontiers in Neuroscience, 2018)
Neurons expressing neuropeptide orexins (hypocretins) in the lateral hypothalamus (LH) and serotonergic neurons in the dorsal raphe nucleus (DR) both play important roles in the regulation of sleep/wakefulness states, and show similar firing patterns across sleep/wakefulness states. Orexin neurons send excitatory projections to serotonergic neurons in the DR, which express both subtypes of orexin receptors (Mieda et al., 2011), while serotonin (5-HT) potently inhibits orexin neurons through activation of 5HT1A receptors (5HT1ARs). In this study, we examined the physiological importance of serotonergic inhibitory regulation of orexin neurons by studying the phenotypes of mice lacking the 5HT1A receptor gene (Htr1a) specifically in orexin neurons (ox5HT1ARKO mice). ox5HT1ARKO mice exhibited longer NREM sleep time along with decreased wakefulness time in the later phase of the dark period. We also found that restraint stress induced a larger impact on REM sleep architecture in ox5HT1ARKO mice than in controls, with a larger delayed increase in REM sleep amount as compared with that in controls, indicating abnormality of REM sleep homeostasis in the mutants. These results suggest that 5HT1ARs in orexin neurons are essential in the regulation of sleep/wakefulness states, and that serotonergic regulation of orexin neurons plays a crucial role in the appropriate control of orexinergic tone to maintain normal sleep/wake architecture.